2021
DOI: 10.1161/circresaha.119.315715
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Joining Region in Junctophilin-2 With the L-Type Ca 2+ Channel Is Pivotal for Cardiac Dyad Assembly and Intracellular Ca 2+ Dynamics

Abstract: Rationale: Ca 2+ induced Ca 2+ release (CICR) in normal hearts requires close approximation of L-type calcium channels (LTCCs) within the transverse tubules (T-tubules), and Ryanodine receptors (RyR) within the junctional sarcoplasmic reticulum (jSR). CICR is disrupted in cardiac hypertrophy and heart failure, which is associated with loss of T-tubules and disruption of cardiac dyads. In these conditions, LTCCs are redistributed from the T-tubules to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 99 publications
1
49
1
Order By: Relevance
“…While EM data have historically indicated that the dyadic cleft measures only ≈12 nm across ( Takeshima et al, 2000 ), recent data have suggested that the true dimensions may be even more narrow (<10 nm), and that artifactual expansion of the cleft could have occurred in earlier work as a result of sample fixation procedures ( Rog-Zielinska et al, 2021a ). Consistent dyadic dimensions are ensured by junctophilin-2 (JPH2) which stabilizes the membranes, but also functionally interacts with both RyRs and LTCCs ( Jiang et al, 2016 ; Munro et al, 2016 ; Reynolds et al, 2016 ; Gross et al, 2021 ). Insight into the precise positioning of these dyadic proteins has been made possible by new advances in super-resolution microscopy, including STED ( Wagner et al, 2012 ), 3d STORM ( Shen et al, 2019 ), and DNA-PAINT techniques ( Jayasinghe et al, 2018 ; Sheard et al, 2019 ).…”
Section: T-tubule Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…While EM data have historically indicated that the dyadic cleft measures only ≈12 nm across ( Takeshima et al, 2000 ), recent data have suggested that the true dimensions may be even more narrow (<10 nm), and that artifactual expansion of the cleft could have occurred in earlier work as a result of sample fixation procedures ( Rog-Zielinska et al, 2021a ). Consistent dyadic dimensions are ensured by junctophilin-2 (JPH2) which stabilizes the membranes, but also functionally interacts with both RyRs and LTCCs ( Jiang et al, 2016 ; Munro et al, 2016 ; Reynolds et al, 2016 ; Gross et al, 2021 ). Insight into the precise positioning of these dyadic proteins has been made possible by new advances in super-resolution microscopy, including STED ( Wagner et al, 2012 ), 3d STORM ( Shen et al, 2019 ), and DNA-PAINT techniques ( Jayasinghe et al, 2018 ; Sheard et al, 2019 ).…”
Section: T-tubule Structure and Functionmentioning
confidence: 99%
“…JPH2 is also reported to modulate LTCC activity, which has important implications for L-type current in HFrEF, where JPH2 expression is lowered ( Jiang et al, 2016 ). Interestingly, recent data from Gross et al (2021) indicate that the “Joining Region” of JPH2 may exert direct effects on the localization of LTCC in t-tubules, indicating that not only the presence of JPH2 but specifically JPH2-LTCC binding is necessary for maintenance of dyadic integrity and Ca 2+ homeostasis.…”
Section: Emerging T-tubule Regulatorsmentioning
confidence: 99%
“…JPH2 is the cardiac isoform of the junctophilins family that stabilizes the cardiac dyads between T-tubule and junctional SR membranes, which is critical for proper intracellular calcium signaling [ 100 ]. JPH2 knockdown leads to T-tubule disruption in developing myocardium and in the adult mouse heart [ 101 , 102 ].…”
Section: Speg and Its Interacting Partnersmentioning
confidence: 99%
“…This all occurs against the backdrop of highly specialized, cardiac sub-domains. JPH-2 is understood to control the structure of the calcium dyad by linking ion channel function to control calcium-induced calcium release [ 27 ], as well as being involved in the maintenance of normal tubular morphology [ 28 ]. BIN-1 is also crucial for the maintenance of ion fluxes in healthy ventricular cardiomyocytes [ 29 ].…”
Section: Electrophysiological Remodeling Of the Heart And Tatsmentioning
confidence: 99%
“…The action of LTCC induces the release of calcium from the RYR2 in a process known as calcium-induced calcium release (CICR). JPH-2 is intrinsically important to the process, as it is involved in the direct link between the LTCC and RYR2 to maintain the process [ 27 ]. This sort of complex should be considered similar to the general structural and molecular compartmentation of βAR by membrane microdomains within the TATS.…”
Section: The Molecular Modulation Of Cardiac Electrophysiology By β-Adrenergic Receptorsmentioning
confidence: 99%